2014
DOI: 10.1002/cssc.201301408
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Performance of Hierarchical Porous Carbon Materials Obtained from the Infiltration of Lignin into Zeolite Templates

Abstract: Hierarchical porous carbon materials prepared by the direct carbonization of lignin/zeolite mixtures and the subsequent basic etching of the inorganic template have been electrochemically characterized in acidic media. These lignin-based templated carbons have interesting surface chemistry features, such as a variety of surface oxygen groups and also pyridone and pyridinic groups, which results in a high capacitance enhancement compared to petroleum-pitch-based carbons obtained by the same procedure. Furthermo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(70 citation statements)
references
References 62 publications
5
65
0
Order By: Relevance
“…Electrochemical techniques have been successfully used for the covalent and non-covalent functionalization of different carbon materials with nitrogen functional groups [21], [22] and polymers [23], [24]. The modification of carbon nanotubes using 4-aminobenzoic acid (4-ABA), 4-aminobenzenesulfonic acid (4-ABSA) and 4-aminobenzylphosphonic acid (4-ABPA) in aqueous solution, is an illustrative example of the potential of this method to functionalize with different heteroatoms [8], [25]- [27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Electrochemical techniques have been successfully used for the covalent and non-covalent functionalization of different carbon materials with nitrogen functional groups [21], [22] and polymers [23], [24]. The modification of carbon nanotubes using 4-aminobenzoic acid (4-ABA), 4-aminobenzenesulfonic acid (4-ABSA) and 4-aminobenzylphosphonic acid (4-ABPA) in aqueous solution, is an illustrative example of the potential of this method to functionalize with different heteroatoms [8], [25]- [27].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…More recently, several papers described the preparation of electric double layer capacitor (EDLC) electrodes from lignin (Hu et al 2014;Ruiz-Rosas et al 2014;Zhang et al 2014). You et al (2015) also reported the preparation of electrodes from fine fibers of acetic acid lignin (AAL) for application in EDLCs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, an intense research on the preparation of materials with controlled pore systems at different length scales has been taking place, since an adequate control of the pore size plays a key role in carbon material properties and performance (Ruiz-Rosas et al, 2014;Saha et al, 2014a). In this context, nanostructured carbons with hierarchical pore arrangement, known as hierarchical porous carbons (HPCs), have shown outstanding behavior in different applications because of the different ranges of interconnected pores.…”
Section: Templated Carbonsmentioning
confidence: 99%
“…This seems to be a consequence of the high concentration of active sites of the carbon fraction generated from the infiltration in the zeolite. These lignin-based templated carbons showed a specific capacitance as high as 250 F/g, at 50 mA/g, with a capacitance retention of 50% and volumetric capacitance of 75 F/cm 3 at currents higher than 20 A/g thanks to their interconnected porous texture (Ruiz- Rosas et al, 2014).…”
Section: Templated Carbonsmentioning
confidence: 99%